INORGANIC OXIDE SYNTHESIS FROM ACEH BOVINE BONE USING THE PRECIPITATION METHOD FOR BIOMASS TRANSESTERIFICATION - Amlia, Nisa; Ramli, Muliadi; Rossani, Ratu Balqis; Mitaphonna, Rara; Lubis, Surya; Idris, Nasrullah; Saiful, Saiful; Fathurrahmi (Walisongo Journal of Chemistry, 2025)
Inorganic oxide nanoparticles synthesized from Aceh bovine bone were successfully prepared using the precipitation method, with pH variations of 8 and 10 adjusted using NH₄OH as the precipitating agent and pH regulator. The resulting nanocatalysts were characterized using XRD, FTIR, and SEM-EDX, and their catalytic activity was evaluated through the transesterification of RBDPO. XRD and FTIR analyses confirmed the presence of hydroxyapatite (Ca₁₀(PO₄)₆(OH)₂), calcium oxide (CaO), and calcium carbonate (CaCO₃) as the main components in catalysts synthesized at pH 8 and pH 10. SEM micrographs revealed spherical particle morphologies, while EDX analysis showed calcium as the dominant element, with contents of 55.44% and 57.19%, respectively. The average crystallite sizes, calculated using the Debye–Scherrer equation, were 31.63 nm (CB-P8C) and 31.31 nm (CB-P10C). Catalytic activity tests demonstrated that the catalyst synthesized at pH 10 exhibited higher performance, achieving a biodiesel yield of 98.11%, compared to 92.66% for the catalyst synthesized at pH 8. Quality assessment of both biodiesel samples confirmed that their acid values, density, and viscosity met the Indonesian National Standard (SNI 04-7182-2015). This approach highlights a sustainable pathway for converting biowaste into efficient catalysts for green fuel production.